SYSTEMATIC REVIEW: DETERMINANTS OF PATIENT SATISFACTION WITH HOSPITAL SERVICES - Ni Putu Deni Adi; Yaslis Ilyas (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Satisfactory and quality service will shape patient or customer loyalty, and satisfaction is closely related to